Causes of perinatal deaths in Ga-Rankuwa Hospital Obstetrics Unit : an autopsy study of 100 cases - Muthuphei, Mufandilani Nelson (Department of Paediatrics and Child Health, 2017)
Introduction: Perinatal mortality is regarded as an indicator of the social status and obstetrical care within a given community. The developed world has witnessed a dramatic decline in perinatal mortality as standards of living improved. Unfortunately, this turn of events has not been seen in the Third World where mortality remains very high. When improved perinatal autopsy techniques are applied the causes of perinatal deaths are readily appreciated. No previous autopsy study has been conducted at our hospital. The application of new techniques has stimulated the present study, which is also intended to monitor current and future clinical practice. Problem formulation: What are the common causes of death in the perinatal period at Ga-Rankuwa Hospital? Aims of the study: a. To assess the common causes of fetal and neonatal deaths at our hospital. b. To determine those causes which are preventable and propose specific obstetric interventions. c. To obtain a baseline for future studies along the same line. d. To lay a foundation for clinicopathologic discussion with clinical colleagues. Research Methodology: An autopsy study is to be conducted on each and every stillbirth and neonatal death that occurs during the period of study. The technique will be discussed in detail in Chapter 3.